Fiber based practical QKD system - Ali, Sellami; Ahmed, Abdallah Hassen; Mohammed, Sellami; Chowdhury, Md. Sazzad Hossien; Hassan Abdalla Hashim, Aisha; Mahmoud, Omer (2012)
A method to estimate parameters of the decoy state method based on one decoy state protocol for both BB84 and SARG04 has been presented. This method has given different lower bound of the fraction of single-photon counts (y1), the fraction of two-photon counts (y2), the upper bound QBER of single -photon pulses (e1), the upper bound QBER of two-photon pulses (e2), and the lower bound of key generation rate for both BB84 and SARG04. The fiber based QKD systems also have been simulated using the proposed method for BB84 and SARG04. The numerical simulation has shown that the fiber based QKD systems using the proposed method for BB84 are able to achieve both a higher secret key rate and greater secure distance than that of SARG04.